In Vitro Evaluation and Comparison of Antibacterial Activity of the Novel Herbal Aqueous Creams Containing Aqueous Extracts of the Leaves of Ficus religiosa L.: Randima T.R.1*, Gajaman P.P.M.1, Wimalasiri Y.S.G.2, Perera P.K.3, Navaratne V.4 and Sanjeewani N.A.1 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
In the current healthcare system, antibiotic resistance has become one of the crucial health issues. Discovering a novel antibiotic is a very complex and time-consuming process. Hence there is an increasing trend of conducting researches using herbal sources to treat infections which are resistant to currently available antibiotics. The objective of this study was to in vitro evaluation and comparison of the antibacterial property of herbal creams containing aqueous extracts of leaves of Ficus religiosa L. against Staphylococcus aureus and Pseudomonas aeruginosa. Ficus religiosa L. is a plant which has been using for many decades in Ayurvedic medicines to treat various types of illnesses including dermatological diseases. In this study, the antibacterial effect of the leaf extract was evaluated using agar well diffusion method. Using a dose-response curve, different concentrations of the extract were selected to formulate herbal creams. According to British Pharmacopoeia 2015, the aqueous cream samples were formulated without adding the preservative. Antibacterial effects of creams were evaluated against S.aureus and P. aeruginosa. The plant extract has shown a promising inhibitory action against the tested organisms. Some higher concentrations of plant extracts have shown a higher Zone of Inhibition when compared with the positive control (Gentamicin 50 ug/mL). All the cream samples have shown more inhibitory action against S. aureus than P. aeruginosa. The stability of the cream samples was evaluated. No change was observed in appearance, color and odor of cream samples in the period of 3 months. The overall results of this study indicate that the herbal creams have promising antibacterial properties and these results could be utilized in the pharmaceuticals industry to carry out more testing procedures to develop as an efficient antibacterial cream. Keywords: Antibacterial property, Antibiotic resistance, Ficus religiosa L., Skin diseases, Formulations, Herbal creams